Innocence on trial: the courts and sexual violence against children in Florence, 1786 to 1914 - Radica, Christel (2017)
This thesis investigates attitudes to sexual violence against children as revealed in penal codes and criminal courts in Florence during the long nineteenth century. The main question is: how did the approach to sexual violence against children shown by institutions of the state, society and family change throughout the so-called century of childhood? The choice of Florence as a case study of child abuse in Italy was made for three main reasons: first, the succession of several régimes –not unusual in Italy during this period- permits me to examine how different governments regulated sexual violence towards children, tracing continuities and changes; second, the considerable attention paid to children, to their health and education, by private and public institutions in Florence throughout the century would lead historians to assume there was a general condemnation of child sexual abuse; last but not least, the widespread historical assumption that Tuscany possessed especially advanced and modern penal codes made me wonder whether Tuscany was also especially progressive in attitudes to sexual violence against children. Given the gulf between law and judicial practice, the latter has been analysed through criminal records. Even though during the body of the thesis sexual violence against girls, and against boys, and within the context of incestuous relationship have been analysed within different sections, in the conclusions they have been brought together offering a nuanced account of varieties of response, while also keeping in mind the central research question.